Investigating the Effects of Recycled Micropowder and Aggregate on the Properties of Cement Stabilization of Crushed Aggregate (CSCA) - Miaoyi Deng; Xiangbing Xie; Kaiwei Wang; Mingwei Wang; Jinggan Shao; Zi Yun Li; Hui Wang (Advances in Materials Science and Engineering)
The recycled powder produced in the process of crushing concrete and brick waste (C&BW) into recycled aggregate will cause environmental pollution. To realize the green full recycling of concrete and brick waste, the cement stabilization of crushed aggregate (CSCA) containing recycled brick-concrete composite micropowder (RBCP) and recycled brick-concrete composite aggregate (RBCA) is proposed. In this paper, RBCP, recycled brick-concrete composite fine aggregate (RBCFA), and recycled brick-concrete composite coarse aggregate (RBCCA) were the recycled materials from C&BW. The orthogonal test table was used to analyze the effects of the three recycled materials on the compaction characteristics, mechanical properties, and shrinkage behavior of CSCA at different dosages. The effects of RBCP, RBCCA, and RBCFA on the properties of CSCA are studied by variance analysis methods. On this basis, the micromorphology and the interface transition zone (ITZ) were studied for CSCA and the cement stabilization of crushed aggregate with RBCP, RBCFA, and RBCCA through scanning electron microscopy with energy dispersive spectroscopy (SEM/EDS), and the mechanism was revealed. The results indicate that the addition of RBCP and RBCA can increase the optimal water content while decreasing the optimal dry density of CSCA, and the influence of RBCCA on the optimal water content is greater than that of RBCFA. Three optimal composite replacement systems for CSCA, including 20% RBCP/20%RBCFA/40%RBCCA, are proposed and have the best mechanical and antishrinkage performance through the range analysis. Furthermore, the variance analysis test results show that RBCCA and RBCFA have the most significant effect on the compressive strength and shrinkage strain properties, while RBCP has the most significant effect on the bending tensile strength. It is found that RBCP played a filling effect and pozzolanic activity in the strength formation of CSCA. The SEM/EDS test shows that the CSCA with recycled materials produced the Ca/Si ratio in the interfacial zone between the cement paste and aggregate lower than the CSCA without recycled materials, the largest decline 52.83%. The research results of this paper can provide the potential application of RBCP and RBCA.